2019
DOI: 10.3389/fnbeh.2019.00198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Enrichment in Maternally Separated Rats: Age and Sex-Specific Outcomes

Abstract: Maternal separation (MS) early in life is related to an increase in anxiety and depressive-like behaviors and neurobiological alterations mostly related to alterations in hypothalamic pituitary adrenal (HPA) axis reactivity. Environmental enrichment (EE) has been used to ameliorate the effects of MS. However, the outcomes of this intervention at different developmental periods after MS have not been studied. We subjected male and female Sprague–Dawley pups to MS and subsequently compared the effects of EE star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…(2021) 26:8 [37][38][39]. Our study also drew a conclusion that learning and memory ability was closely related to the time of escape latency and the number of crossing the platform in Morris water maze; the frequency of required training and the rate of correct response in Y-maze was redressed after living in an enriched environment.…”
Section: Guan Et Al Environmental Health and Preventive Medicinementioning
confidence: 51%
“…(2021) 26:8 [37][38][39]. Our study also drew a conclusion that learning and memory ability was closely related to the time of escape latency and the number of crossing the platform in Morris water maze; the frequency of required training and the rate of correct response in Y-maze was redressed after living in an enriched environment.…”
Section: Guan Et Al Environmental Health and Preventive Medicinementioning
confidence: 51%
“…EE (for 28 days) in late adolescence after postnatal stress could restore behavioral function at adulthood (O'Mahony et al, 2011). It also enhanced social behavior in rats prenatally exposed to stress (Doreste-Mendez et al, 2019). Dandi et al demonstrated that EE (for 6 weeks) protected against detrimental effects of MS on memory and anxiety at adulthood (Dandi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a single episode of prolonged MS is enough to increase both basal and stress-induced levels of corticosterone (CORT) and adrenocorticotropic hormone (O'Mahony et al, 2011). MS could induce upregulation of corticotrophin-releasing hormone (CRH) gene expression, downregulation of CRH receptors and hippocampal glucocorticoid receptors (Doreste-Mendez et al, 2019). These receptors are involved in the negative feedback of stress response (Anisman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…EE during adolescence was effective in restoring normal hippocampal-dependent behaviour, AHN and neuronal activation following ELS. A number of studies demonstrate the benefit of EE throughout adolescence for restoring HPA axis function, learning and memory, anxiety, fear, social performance, attention, depressive-like behaviours, amygdala activity and hippocampal LTP following maternal separation or limited nesting and bedding in the early post-natal period [23][24][25][83][84][85] . One recent study investigated the effects of exposure to EE during adolescence, directly following PPS, and found this prevents stress vulnerability and normalises anxiety-like behaviour after adult traumatic stress.…”
Section: Discussionmentioning
confidence: 99%